2016
DOI: 10.1084/jem.20151289
|View full text |Cite
|
Sign up to set email alerts
|

Arid5a regulates naive CD4+ T cell fate through selective stabilization of Stat3 mRNA

Abstract: Balance in signal transducer and activator of transcription (STAT) activation is a key factor in regulating the fate of naive CD4+ T cells. Here, we demonstrate that AT-rich interactive domain-containing protein 5a (Arid5a) in T cells directs naive CD4+ T cells to differentiate into inflammatory CD4+ T cells, especially Th17 cells, through selective stabilization of Stat3 (but not Stat1 and Stat5) mRNA in an IL-6–dependent manner. Loss of Arid5a in T cells led to reduction of STAT3 level under Th17-polarizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
103
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 51 publications
10
103
1
Order By: Relevance
“…Arid5a deficiency was shown to inhibit the elevation of IL-6 serum levels in LPS-treated mice (11). Our recent study also showed an intrinsic role for Arid5a in T cells, where Arid5a was found to direct the differentiation of naive CD4 + T cells into inflammatory CD4 + T cells by the stabilization of STAT3 mRNA (12). Overall, these findings suggest Arid5a has an important immune regulatory function.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…Arid5a deficiency was shown to inhibit the elevation of IL-6 serum levels in LPS-treated mice (11). Our recent study also showed an intrinsic role for Arid5a in T cells, where Arid5a was found to direct the differentiation of naive CD4 + T cells into inflammatory CD4 + T cells by the stabilization of STAT3 mRNA (12). Overall, these findings suggest Arid5a has an important immune regulatory function.…”
supporting
confidence: 58%
“…Arid family proteins are believed to have DNA-binding properties (18), but our group demonstrated that Arid5a can function as an RNA-binding protein (11,12). Thus, there is a possibility that Arid5a could regulate T-bet and IFN-γ transcriptionally, by activating their promoters, or posttranscriptionally, by activating their UTRs.…”
Section: Ifn-γ and T-bet Expression Is Significantly Decreased In Arimentioning
confidence: 98%
See 2 more Smart Citations
“…Collectively, these findings strongly suggest that modulation of IL-6 post-transcription is related to pathogenesis of sepsis. Additionally, we found the significant involvement of Arid5a in the differentiation of naïve helper T (Th) cells into Th17 cells in a murine experimental autoimmune encephalomyelitis (EAE) model, by controlling by stability of STAT3 mRNA [13].…”
mentioning
confidence: 96%